Inclusão e universidade: uma análise a partir da perspectiva de discentes travestis e transexuais da Universidade Federal de Goiás - Machado, Kamyla Aparecida Gomes (2021)
This research analyze transsexual students’ point of view in relation to their inclusion and permanence at the Federal University of Goiás (UFG). A qualitative research was made within a theoretical basis and practical survey about transsexuality, transvestility, prejudice and dialectic inclusion/exclusion. It is noticed that transidentities (travestis and transsexuals) have always been part of humanity although they are marginalized throughout history. Today they have gained greater visibility and have occupied several spaces. However, exclusion continues affecting their right to citizenship as trans people and also have a strong impact on their individual and collective journeys. This whole process requires inclusion of these people in places that represent power and decision, including the university. The research made in the university is justified by its role as a place that produces knowledge and bring us to consider critical thinking and reflect about attitudes. That is why this field is propitious to receive and help the trans public receive education for the community, therefore break the prejudices that exists within this topic. The data for analysis were obtained from four semi-structured interviews with travestis and transsexual students at the institution. In the discussion based on the Critical Theory of Society, by Horkheimer and Adorno, we tried to understand some writers thoughts concerning inclusion/exclusion and also the perspective shown by media and society on the aspects on this specific subject. This research was divided into three chapters. The first is directly related to transidentities, the second works the dialectic inherent within the issue and the third analyzes the interviews that were made. As a result of this research it was possible to see that UFG is aware about the trans community needs and that affirmative actions and student assistance are working together to support this community despite problems such as budget cuts. However, UFG still needs to expand and improve trans people inclusion.